A comparative analysis of postpartum maternal mental health in women following spontaneous or ART conception. (June 2014) - Listijono, Dave R.; Mooney, Samantha; Chapman, Michael
Abstract Objective: To determine whether conception following assisted reproductive technology (ART) predisposes women to increased risk of postnatal depression (PND), compared to women who conceived naturally, when controlling for such factors as: multiple birth, previous maternal psychiatric history and sociodemographic status. Participants: A total of 200 women who attended the private antenatal and fertility clinics of a fertility specialist in a large Australian city between January 2009 and December 2011 were contacted via telephone. Results: There was no difference in the rate of PND between the two groups (7.5% versus 7.4%, p = ns). Aside from the slightly older maternal age in the ART group (35.4 versus 33, p < 0.05), baseline socio-demographics were similar. There was a significantly higher rate of previous maternal clinical depression in the ART group compared to the controls (17% versus 5%, p < 0.05); however, other known risk factors for PND, including previous PND (10.6% versus 13.7%, p = ns), multiple births (2.1% versus 4.2%, p = ns) and low infant birth weight (3.3 kg versus 3.4 kg, p = ns), were not different in the two cohorts. Women who conceived naturally were also more likely to breastfeed for a longer duration (78% versus 89%, p < 0.05). Conclusion: Our study demonstrates that when accounting for well-known risk and protective factors for postpartum depression, women who conceive using ART are not at an increased risk PND. In addition, the low rate of multiple births in the ART group further validates the practice of single embryo transfer.